Understanding property rights - Meinzen-Dick, Ruth S.; Pradhan, Rajendra; Di Gregorio, Monica (International Food Policy Research Institute, 2004)
The authors describe property rights as overlapping 'bundles' of rights, which can be grouped as use rights and control or decisionmaking rights. The authors then explain the concept of legal pluralism or many sources of rights and the implications for property rights. -- from Text.